Selling souls: an empirical analysis of human trafficking and globalization - M. Tariq Majeed; Amna Malik (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
This paper investigates the impact of globalization on human trafficking using a large panel data set of 169 countries from 2001 to 2011. This study explores the contribution of economic, social and political globalization in the trafficking of humans for forced prostitution, forced labor, debt bondages and child soldiers. Moreover, the study investigates the impact of globalization on source (supply) and destination (demand) of human trafficking. This study uses Probit and Oprobit models of panel data for empirical analysis. Findings of the study show that globalization facilitates human trafficking, particularly, forced prostitution, forced labor and debt bondages while it helps to suppress the demand and supply of child soldiers. The empirical analysis also reveals that these are the mostly poor countries which serve as source of human trafficking while the rich countries are destination of trafficked victims. The data series over a long period are not available and therefore the sample size is small. This research paper contributes into the literature on human trafficking and globalization by highlighting the heterogeneity of source and destiny economies in shaping the links of globalization with human trafficking. To the best of our knowledge, it is first study of its kind that provides an empirical analysis of source and destiny of human trafficking with globalization. Moreover, this study considers different dimensions of globalization and human trafficking. The main message of this research is that as globalization proceeds, human trafficking increases. Therefore, the governments of developing economies need to improve socioeconomic conditions to provide basic necessities of life at home country and the governments of developed countries need to implement strong rule of the law to discourage such practices. Our study is useful in offering insights to policy makers that how to avoid the perils of globalization.
Keywords: 330; Human trafficking; globalization; human smuggling; probit and oprobit model